Effects of nitrogen and phosphorus additions on soil methane uptake in disturbed forests. Issue 12 (23rd December 2016) - Zheng, Mianhai; Zhang, Tao; Liu, Lei; Zhang, Wei; Lu, Xiankai; Mo, Jiangming
Abstract: Atmospheric nitrogen (N) deposition is generally thought to suppress soil methane (CH4 ) uptake in natural forests, and phosphorus (P) input may alleviate this negative effect. However, it remains unclear how N and P inputs control soil CH4 uptake in disturbed forests. In this study, soil CH4 uptake rates were measured in two disturbed forests, including a secondary forest (with previous, but not recent, disturbance) and a plantation forest (with recent continuous disturbance), in southern China for 34 months of N and/or P additions: control, N addition (150 kg N ha −1  yr −1 ), P addition (150 kg P ha −1  yr −1 ), and NP addition (150 kg N ha −1  yr −1 plus 150 kg P ha −1  yr −1 ). Mean CH4 uptake rate in control plots was significantly higher in the secondary forest (24.40 ± 0.81 µg CH4 ‐C m −2  h −1 ) than in the plantation forest (17.07 ± 0.70 µg CH4 ‐C m −2  h −1 ). CH4 uptake rate had negative relationships with soil water‐filled pore space in both forests. In the secondary forest, N, P, and NP additions significantly decreased CH4 uptake by 39.7%, 27.8%, and 37.6%, respectively, but had no significant effects in the plantation forest, indicating that P input does not alleviate the suppression of CH4 uptake by N deposition. Taken together, our findings suggest that reducing anthropogenic disturbance, including harvesting of forest floor, and anthropogenic N and P inputs will increase soil CH4 uptake in disturbed forests, which is important in view of the increased trends in global warming during recent decades. Key Points: Soil methane fluxes were measured following N and P additions in two disturbed forests N and/or P additions reduced methane uptake in secondary forest but not in plantation forest Anthropogenic disturbance is responsible for the reduced soil methane uptake in disturbed forests